Between Heaven and Earth: The Common Core of Basic Formal Ontology (Advances in Knowledge Representation, 2025)
This paper critically examines the relationship between Basic Formal Ontology (BFO) and the Common Core Ontologies (CCO), offering a comprehensive discussion of their theoretical foundations, design patterns, and implementation practices. The paper highlights BFO’s commitment to realism, perspectivalism, fallibilism, and adequatism, and illustrates how these principles guide the representation of domain-specific entities within CCO. The modular structure of CCO is analyzed, emphasizing its eleven component ontologies and the hub-and-spoke strategy that promotes semantic integration across diverse domains. The paper also engages with practical challenges in distinguishing between TLOs, MLOs, and domain ontologies, proposing heuristic and formal criteria for delineating their scope. Using a dataset from the US Federal Aviation Administration, the paper demonstrates CCO’s modeling capabilities, particularly in integrating design specifications and real-world data. The study concludes by underscoring the importance of aligning data quality and semantic interoperability in ontology engineering, and it calls for sustained methodological rigor and collaboration to advance the BFO-CCO ecosystem.